Late Language Emergence at 24 Months: An Epidemiological Study of Prevalence, Predictors, and Covariates - Zubrick, Stephen R; Taylor, Catherine; Rice, M.; Slegers, D. (American Speech-Language-Hearing Association, 2007)
The primary objectives of this study were to determine the prevalence of late language emergence (LLE) and to investigate the predictive status of maternal, family, and child variables.Method: This is a prospective cohort study of 1,766 epidemiologically ascertained 24-month-old singleton children. The framework was an ecological model of child development encompassing a wide range of maternal, family, and child variables. Data were obtained using a postal questionnaire. Item analyses of the 6-item Communication scale of the Ages and Stages Questionnaire (ASQ; D. Bricker & J. Squires, 1999; J. Squires & D. Bricker, 1993; J. Squires, D. Bricker, & L. Potter, 1997; J. Squires, L. Potter, & D. Bricker, 1999) yielded a composite score encompassing comprehension as well as production items. One SD below the mean yielded good separation of affected from unaffected children. Analyses of bivariate relationships with maternal, family, and child variables were carried out, followed by multivariate logistic regression to predict LLE group membership. Results: 13.4% of the sample showed LLE via the ASQ criterion, with 19.1% using the single item of "combining words." Risk for LLE at 24 months was not associated with particular strata of parental educational levels, socioeconomic resources, parental mental health, parenting practices, or family functioning. Significant predictors included familial history of LLE, male gender, and early neurobiological growth. Covariates included psychosocial indicators. Results are congruent with models of language emergence and impairment that posit a strong role for neurobiological and genetic mechanisms of onset that operate across a wide variation in maternal and family characteristics.